Transformations of the economic structure of overseas departments of France as a consequence of the global economic crisis - Dorocki, Sławomir; Brzegowy, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The intention of the article is to present the transformations in the diversification of the economic structures in overseas France, the DOM-TOM (Guadeloupe, Martinique, French Guiana and Reunion) in comparison to metropolitan France, during the global economic crisis. This article is an attempt to answer the question: whether, and to what extent the financial crisis of 2008 has affected the overseas economy and to what extent the changes that were observable in the last several years in the industrial production structure and services such as the third phase of the industrial revolution, have been affected in the aftermath of the global recession. Reflection of the progressive transformation in the overseas departments of France is the gradual reduction of employment in agriculture and growing employment in industry and services as well as the development of technologies de pointe (high-tech industry). An example of these changes is the tourism industry developed since the 1960s, that today is trying to become the fundamental substrate of the economies of the Overseas France. In order to illustrate the economic activity of these territories, the following factors were analyzed: the increase in the unemployment rates and changes in size and structure of employment, including changes in the volume of self-employment and business bankruptcies during the period before and after 2008.